Relevance of Membrane Contact Sites in Cancer Progression - Gil-Hernández, Aurora; Arroyo-Campuzano, Miguel; Simoni-Nieves, Arturo; Zazueta, Cecilia; Gomez-Quiroz, Luis Enrique; Silva-Palacios, Alejandro (Frontiers in Cell and Developmental Biology, 2021)
Membrane contact sites (MCS) are typically defined as areas of proximity between heterologous or homologous membranes characterized by specific proteins. The study of MCS is considered an emergent field that shows how crucial organelle interactions are in cell physiology. MCS regulate a myriad of physiological processes such as apoptosis, calcium, and lipid signaling, just to name a few. The membranal interactions between the endoplasmic reticulum (ER)-mitochondria, the ER-membrane plasmatic, and the vesicular traffic have received special attention in recent years particularly in cancer research, in which it has been proposed that MCS regulate tumor metabolism and fate, contributing to their progression. However, as the therapeutic or diagnostic potential of MCS has not been fully revisited, in this review, we provide recent information on MCS relevance on calcium and lipid signaling in cancer cells and on its role in tumor progression. We also describe some proteins associated with MCS, like CERT, STIM1, VDAC, and Orai, that impact on cancer progression and that could be a possible diagnostic marker. Overall, these information might contribute to the understanding of the complex biology of cancer cells.